Revision of the Derbidae of Seychelles Islands (Insecta: Hemiptera: Fulgoromorpha) - Löcker, Holger; Löcker, Birgit; Holzinger, Werner E. (Zootaxa, 2009)
The Derbidae fauna of the Seychelles is revised, providing redescriptions for the following species: Aquaelicium brunnescens Distant, 1917, A. elegantulum Distant, 1917, A. typicum Distant, 1917, Equirria phalaena Distant, 1917, Fordicidia robusta Distant, 1917, Paraphenice aurea (Distant, 1917), P. bimaculata (Distant, 1917), Proutista moesta (Westwood, 1851) and Sikaiana albomaculata (Distant, 1917). A new species, Vekunta bri sp. nov., increases the number of derbid taxa known from the Seychelles to 10 species in 7 genera. Lectotypes are designated for the following species: A. typicum, A. brunnescens, A. elegantulum, F. robusta and S. albomaculata. A key to derbid tribes and species of Seychelles is provided.